2012
DOI: 10.1186/1477-3155-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles as high-resolution X-ray imaging contrast agents for the analysis of tumor-related micro-vasculature

Abstract: BackgroundAngiogenesis is widely investigated in conjunction with cancer development, in particular because of the possibility of early stage detection and of new therapeutic strategies. However, such studies are negatively affected by the limitations of imaging techniques in the detection of microscopic blood vessels (diameter 3-5 μm) grown under angiogenic stress. We report that synchrotron-based X-ray imaging techniques with very high spatial resolution can overcome this obstacle, provided that suitable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 40 publications
1
46
0
1
Order By: Relevance
“…[15][16][17][18][19] Nanoparticles can extravasate from the leaky tumor vessels and accumulate in tumor tissues. 20,21 However, the uptake and cellular response of solid tumor cells to USPIONs has not been clearly investigated. As a result, the goals of the present study were to determine whether: (1) breast cancer cells have increased nanoparticle uptake compared to normal cells, (2) nanoparticle size and surface coating affects the uptake and cellular responses of the particles, (3) nanoparticles cause toxicity to normal and breast cancer cells, and (4) if there are any differences in MRI contrast resulting from differential uptake in breast cancer cells compared to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Nanoparticles can extravasate from the leaky tumor vessels and accumulate in tumor tissues. 20,21 However, the uptake and cellular response of solid tumor cells to USPIONs has not been clearly investigated. As a result, the goals of the present study were to determine whether: (1) breast cancer cells have increased nanoparticle uptake compared to normal cells, (2) nanoparticle size and surface coating affects the uptake and cellular responses of the particles, (3) nanoparticles cause toxicity to normal and breast cancer cells, and (4) if there are any differences in MRI contrast resulting from differential uptake in breast cancer cells compared to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of using nanomedical imaging technology currently is in cancer detection. Recently Chien et al reported that administration of gold nanoparticle together with heparin produced contrast in X-ray imaging which was suffi cient to see tumour microvessel (3-5 μm diameter) or extravascular diffusion [ 40 ]. For MRI contrast agents, the use of iron oxide nanoparticles is a classic example.…”
Section: Point-of-care (Poc) Medical Diagnostic Devicesmentioning
confidence: 98%
“…In 2012, Chien et al 156 used AuNPs as high-resolution X-ray imaging contrast agents for analysis of tumor-related micro-vasculature. 156 AuNMs hold great interest in imaging field thanks to their characteristics such as mono dispersity, stability, minimal toxicity and excellent contrasting for transmission electron microscopy (TEM) analysis, which enable tracking with unprecedented resolution on dynamic of uptake, intracellular sorting and potential secretion. 157,158 Figure 8 Scheme of the developed method for detection of DNA methylation and assay of DNA methyltransferase activity.…”
Section: Aunms Based Imagingmentioning
confidence: 99%